Augmentation of Labour- A Comparison of Oral Misoprostol and Intravenous Titrated Oxytocin Infusion - Maliha Sadaf, Shagufta Saeed Sial, Sobia Nawaz Malik (Journal of Rawalpindi Medical College, 2013)
Background: To compare oral misoprostol with intravenous oxytocin for labour augmentation in nulliparous women . Methods: Women(n=500) with regular contractions and an effaced cervix dilated between 3 and 9 cm, and who had inadequate uterine contractions (two or fewer contractions every 10 minutes) during the first stage of labour, were augmented with 75 μg oral misoprostol (single dose) or intravenous oxytocin. The primary parameters used to evaluate efficacy of misoprostol were the interval from the beginning of augmentation to vaginal delivery and the percentage of women who delivered their newborns vaginally within 6 to 12 hours of this interval. The primary parameters used to evaluate adverse events were incidence of tachysystole, hypertonus and uterine hyperstimulation. The secondary parameters used to evaluate efficacy or adverse events were rates of cesarean births, failure to progress and fetal distress.The neonatal outcomes included low Apgar score (less than 7 at 5 minutes after birth) and admission to the neonatal intensive care unit (NICU). Statistical significance was given to p< 0.05. Results: Of the 500 women, 250 were augmented with 75 μg oral misoprostol and 250 with titrated intravenous oxytocin. The mean interval from the beginning of augmentation to vaginal delivery was 6.53 hours in the misoprostol group, and 6.01 hours in the intravenous oxytocin group. Complete vaginal delivery occurred within 6 hours in 102 women (48.11%) in the misoprostol group and in 93 women (46.03%) in the oxytocin group (p value 0.647). There was no significant difference between the two groups who delivered vaginally within 12 hours. Side effects and neonatal outcomes also did not differ significantly between the two groups. Conclusion: Oral misoprostol may be an acceptable alternative to the traditional oxytocin for augmentation of labour.